2021
DOI: 10.1158/2159-8290.cd-20-1114
|View full text |Cite
|
Sign up to set email alerts
|

RB/E2F1 as a Master Regulator of Cancer Cell Metabolism in Advanced Disease

Abstract: Loss of the retinoblastoma (RB) tumor suppressor protein is a critical step in reprogramming biological networks that drive cancer progression, although mechanistic insight has been largely limited to the impact of RB loss on cell cycle regulation. Here, isogenic modeling of RB loss identified disease stage-specific rewiring of E2F1 function, providing the first-in-field mapping of the E2F1 cistrome and transcriptome after RB loss across disease progression. Biochemical and functional assessment using both in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 72 publications
(79 reference statements)
1
47
0
Order By: Relevance
“…The first major finding is that two key transcriptional regulators involved in carcinogenesis, FOXM1 and E2F1, are reduced in cells with TRPM2 deletion compared to control cells 38 , 55 . FOXM1 is expressed in highly proliferative cells including progenitor cells and regenerating tissue, and both FOXM1 and E2F1 are master regulators in cancer 38 40 , 56 . FOXM1 has a key role in promoting tumor cell proliferation, cell cycle progression, DNA damage repair, angiogenesis, and drug resistance, and elevated FOXM1 correlates with poor prognosis in many cancers 38 , 39 , 57 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first major finding is that two key transcriptional regulators involved in carcinogenesis, FOXM1 and E2F1, are reduced in cells with TRPM2 deletion compared to control cells 38 , 55 . FOXM1 is expressed in highly proliferative cells including progenitor cells and regenerating tissue, and both FOXM1 and E2F1 are master regulators in cancer 38 40 , 56 . FOXM1 has a key role in promoting tumor cell proliferation, cell cycle progression, DNA damage repair, angiogenesis, and drug resistance, and elevated FOXM1 correlates with poor prognosis in many cancers 38 , 39 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…E2F transcription factors, CREB, and HIF-1/2α all promote FOXM1 transcription and expression 38 , 39 . E2Fs, particularly E2F1, also function as master regulators in cancer and regulate a number of pathways which promote proliferation 40 .…”
Section: Introductionmentioning
confidence: 99%
“…We first examined the chromatin binding of p130 in C4-2-tet-shRB cells using ChIP-seq analyses. In the untreated cells, the majority of Rb-binding sites ($80%) and E2F1-binding sites 28 ($60%) were overlapped with p130 binding ($25% and $70% of its total binding sites, respectively; Figures 3A and 3B), suggesting that p130 may function alternatively to Rb to form complexes with E2Fs. Examining several previously identified Rb-binding sites, we confirmed the occupancy of p130, which can be similarly enhanced by the androgen treatment (Figure S6B).…”
Section: Rb Mediates Ar Repression Of E2f Signaling and Cell Cycle Pr...mentioning
confidence: 99%
“…RB1 loss leads to an expansion of E2F1 cistrome, increased redox metabolism, and lineage plasticity, and is associated with the resistance to ARsignaling-inhibition therapies. [24][25][26][27][28] Our previous studies have shown that AR can recruit hypophosphorylated Rb to DNA replication gene loci and strengthens the activity of Rb-E2F suppressor complex. 5 However, it is still unclear how Rb globally mediates this transcriptional repressor activity of AR in CRPC and whether enhancing Rb-E2F transcriptional repression activity can exploit the tumor-suppressive function of high-T in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…SCLC is most notably characterized by loss of RB1 and P53, both of which regulate various metabolic pathways (Table 1) (28,(73)(74)(75), therefore the observation of metabolic differences based on these alone would not provide unique and targetable pathways. Metabolically, the most well studied subcategories of SCLC are driven by ASCL1 and MYC expression.…”
Section: Small Cell Lung Cancermentioning
confidence: 99%